IMPLEMENTASI FUNGSI MANAJEMEN PENDIDIKAN ISLAM DALAM PROGRAM LITERASI AL QUR’AN UNTUK PENGUATAN KARAKTER SISWA DI MTS AL HUDA BANDUNG - Jaswadi, Jaswadi; Junaris, Imam (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service was initiated in response to the urgent need for strengthening character education in Islamic schools that currently face the challenges of globalization, modernization, and the moral decline among students. MTs Al Huda Bandung was selected as the partner institution due to its strong commitment to cultivating a religious culture grounded in the values of the Qur’an. The Qur’anic literacy program was designed as a managerial strategy to habituate students to read, understand, and internalize the teachings of the Qur’an into their daily behavior. The planning stage included the formulation of school policies, teacher training through the Ummi method of Qur’anic recitation to ensure standardized sanad, and the provision of Qur’ans and other supporting facilities. The program was implemented daily, from Monday to Friday at 07:30–09:10, with core activities including recitation of the Qur’an with tartil, memorization of Arabic vocabulary, memorization of selected hadiths, and Arabic writing practice. Teachers played an active role as guides, while students were fully involved through habituation and gradual mentoring. The outcomes demonstrated significant improvements in Qur’anic literacy skills, discipline, responsibility, religiosity, and social solidarity among students. Furthermore, the program fostered the development of a sustainable religious school culture, encouraged parental involvement in Qur’anic habituation at home, and built stronger collaboration between the school and the surrounding community. The future development of the program is directed toward the utilization of digital technology to enhance accessibility and effectiveness, as well as the strengthening of partnerships with educational stakeholders. Thus, the Qur’anic literacy program serves not only as a school routine but also as a strategic instrument in shaping an Islamic generation with strong character, noble morals, and readiness to face modern civilizational challenges. ABSTRAKPengabdian kepada masyarakat ini dilatarbelakangi oleh urgensi penguatan karakter pendidikan di madrasah yang saat ini menghadapi tantangan globalisasi, modernisasi, serta menurunnya moralitas peserta didik. Madrasah Tsanawiyah (MTs) Al Huda Bandung dipilih sebagai mitra karena memiliki komitmen tinggi dalam membangun budaya religius yang berlandaskan nilai-nilai Al-Qur'an. Program literasi Al-Qur'an dirancang sebagai strategi manajerial untuk membiasakan siswa membaca, memahami, dan menginternalisasikan ajaran Al-Qur'an ke dalam perilaku sehari-hari. Perencanaan kegiatan dilakukan secara terstruktur, meliputi penyusunan kebijakan madrasah, pelatihan guru melalui program tahsin metode Ummi untuk penyetaraan sanad bacaan, serta penyediaan fasilitas berupa mushaf dan sarana pendukung lainnya. Pelaksanaan kegiatan berlangsung setiap hari Senin hingga Jumat pada pukul 07.30–09.10 dengan aktivitas utama berupa membaca Al-Qur'an secara tartil, penghafalan kosa kata bahasa Arab, hafalan hadis pilihan, dan pelatihan menulis bahasa Arab. Guru berperan aktif sebagai pembimbing, sementara siswa dilibatkan secara penuh melalui sistem pembiasaan dan bimbingan bertahap. Dampak kegiatan ini terlihat pada peningkatan keterampilan literasi Alquran, penguatan nilai disiplin, tanggung jawab, religiusitas, serta solidaritas sosial antar siswa. Selain itu, kegiatan ini juga mendorong terbentuknya budaya sekolah yang religius, partisipasi orang tua dalam mendukung pembiasaan di rumah, serta terciptanya sinergi positif antara madrasah dan masyarakat sekitar. Prospek program pengembangan diarahkan pada pemanfaatan teknologi digital untuk memperluas akses dan efektivitas kegiatan, serta penguatan kolaborasi dengan pemangku kepentingan pendidikan. Dengan demikian, program literasi Al-Qur'an ini tidak hanya menjadi agenda rutin madrasah, tetapi juga menjadi instrumen strategi dalam membangun generasi Islami yang berkarakter, berakhlak mulia, dan siap menghadapi tantangan peradaban modern.